Homossexualidade e Direitos Humanos (III, IV) - Soares da Costa, Wellington (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The objective of this study is to analyze the granting of pension for homosexual partner of a public servant governed by Law No. 8112/1990. Because it is not guided by statistics, but the interpretation of Brazilian law, the present research is qualitative and it used two technical procedures: literature search and information retrieval. The conclusion is that the legal provisions relevant to the subject material is constitutional and should be interpreted according to the Constitution and that since proven stable, the Government must grant the pension.
Keywords: Law No. 8112/1990; pension; homosexual partner; dignity of human person; equality; analogy